(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
In the Aeneid, Virgil invents the character of the puer who, wishing to fight like a warrior (iuuenis) and to show himself to be a worthy hero (uir), ends up being overthrown by a maior hostis. The essay presents a comparative analysis of these figures and reflects on the possible reasons that led Virgil to insist so much on them.